‘ECONOMIC CONSTITUTION’ IN PRACTICE: THE ENFORCEMENT OF COMPETITION LAW IN ALBANIA - BROKA, Petrina; NAZIFI, Ermal (Journal of Advanced Research in Law and Economics; Vol 2 No 4 (2011): JARLE, Volume II, Issue 2(4), Winter 2011, 2017)
Proper enforcement of competition rules is one of the pillars of the free market economy of Albania. It is also a very important factor for the integration of Albania in the EU. Therefore these rules have been considered as an economic constitution. The effective enforcement of competition rules can be done by public institutions via administrative procedures (public enforcement) or directly by the parties affected from breaches of competition  law by actions in courts (private enforcement). In the case of Albania, public enforcement has been in a process of continuous evolution. On the other hand there have been no cases of private enforcement so far despite the potential of such cases especially in actions for damages following on the decisions of the Albanian Competition Law. However more effort is needed in such areas as the collection of fines, acceptance of recommendations from the part of the government, etc.  For a fully effective implementation of competition rules all institutional stakeholders, the courts and businesses should be engaged in order to contribute positively for the development of the Albanian economy.